Bauran Promosi Di Hisana Fried Chicken Cabang Jakarta Utara - Resti Rohayati; Chandra Ayu Pramestidewi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to analyze the implementation of the promotional mix at Hisana Fried Chicken, North Jakarta Branch, in order to increase sales performance and business competitiveness. The method used in this Field Work Practice (KKL) includes direct observation, interviews, discussions, and analysis of the company’s marketing activities. The results indicate that Hisana Fried Chicken North Jakarta Branch has implemented several elements of the promotional mix, including advertising, sales promotion, personal selling, direct marketing, and public relations. However, advertising and public relations activities have not been optimally implemented in terms of planning, coverage, and sustainability. This condition has contributed to the inconsistency in achieving monthly revenue targets. Therefore, an integrated, sustainable, and evaluation-based promotional mix strategy is required to improve promotional effectiveness, strengthen brand image, and increase sales performance in the future.